Perceived barriers and enablers for implementing water protocols in acute stroke care: A qualitative study using the Theoretical Domains Framework. (4th May 2019) - Barker, Allison; Doeltgen, Sebastian; Lynch, Elizabeth; Murray, Joanne
Abstract: Purpose : To identify perceived enablers and barriers that may influence the implementation of water protocols (WPs) as an intervention for dysphagia in acute stroke settings. Method : Semi-structured interviews were conducted with nine nurses, eight speech-language pathologists (SLPs), five doctors and four dietitians working in acute stroke units in a major city in Australia. Data were thematically analysed and themes were mapped to the Theoretical Domains Framework. Result : Ten barriers and nine enablers were identified. Key barriers were: nurses lack oral care skills and agency nurses lack stroke-specific skills; only SLPs are perceived to be involved with WPs; WP rules will not get followed and may lead to adverse patient outcomes; WPs increase nursing workload; transient workforce impacts efficiency of implementation; and established culture of using thickened fluids. Key enablers were: patients would benefit from WPs; communication and education systems are already in place; acute hospital brings unique benefits; and peer support and modelling support implementation. Conclusion : The perceptions of barriers and enablers to implementation of WPs can be used to inform future studies designed to evaluate the safety and efficacy of WPs and subsequently facilitate their uptake in acute stroke as an alternate dysphagia management strategy.